PEMERIKSAAN HB DAN PEMBERIAN TABLET FE GRATIS SEBAGAI UPAYA PENCEGAHAN ANEMIA PADA IBU HAMILDI POSYANDU OGAN JAYA - Era Mardia Sari; Anggraini, Helni; Amallia, Siti; Rohmin, Anur; Mariyam, Nelly; Rosdiana, Meta; Ratnawati, Ramesia (Ukhuwah : Jurnal Pengabdian Kepada Masyarakat, 2025)
Pregnant women are highly susceptible to pregnancy complications, such as anemia. Anemia in pregnancy is largely caused by iron (Fe) deficiency due to insufficient dietary Fe intake or excessive Fe loss from the body, for example through bleeding. The incidence of anemia in pregnant women can be reduced in various ways, one of which is by providing health education to pregnant women about anemia. The impact of anemia on pregnant women causes various problems, including the risk of giving birth to stunted children. Stunting is a condition where a child's height is shorter than the standard for their age due to ongoing malnutrition. The purpose of this activity was to determine the hemoglobin levels of pregnant women and provide free Fe tablets to pregnant women as an effort to prevent anemia during pregnancy at the Integrated Health Post (Posyandu). The method used was hemoglobin testing and distribution of free iron tablets. This activity was held at the Ogan Jaya Integrated Health Post (Posyandu) on October 25, 2024, with 12 pregnant women participating. The results obtained from 12 pregnant women included 7 with normal hemoglobin levels and 5 with mild anemia. Ten iron tablets were distributed to the pregnant women. This activity is expected to help pregnant women understand their hemoglobin levels and receive Fe tablets as a preventative measure for anemia during pregnancy at the Integrated Health Post (Posyandu).